'The West Welcomes Refugees': Community art as a location of culture. (1st December 2013) - Wyatt, Danielle
'The West Welcomes Refugees' is a government initiated public art project featuring the stories of eleven different migrants and refugees who have settled in Footscray, an old industrial neighbourhood in Melbourne's inner West. For the cultural researcher, this project invokes multiple terms of reference for situating and interpreting the work. As 'community art' it can be framed variously as art instrumentalized for governmental agendas, an organic expression of 'community', a social critique of the nation and a poetic reflection on place. This article engages with the unwieldy and contradictory nature of this project by conceiving of it as a complex location of culture, a term borrowed from Homi Bhabha. Bhabha brings a performative understanding to the relationship between community, culture and place. This framing opens up the social and postcolonial politics of 'The West Welcomes Refugees' in ways not possible within the theoretical terms currently dominating community arts discourses.